Hubungan Tingkat Pemenuhan Kebersihan Diri dengan Tingkat Kepuasan Pasien Immobilisasi - I Ketut Suardana, Ni Made Wedri, I G.A. Oka Mayuni (Berita Kedokteran Masyarakat (BKM), 2007)
Background: Self care are the activity where initiated and be done by a person to involving self need and life saving. At Sanglah hospital nursing treatment for personal hygiene serviced by a nurse and actually be done by their family. Muninjaya founded  patient unsatisfied with nursing services at Sanglah Hospital  di RSUP Sanglah Denpasar. The objective of this study was to describe correlation degree of personal hygiene services with satisfaction of the patient immobilization at Sanglah Hospital.Method: The study was as a descriptive with cross sectional designed that involved 78 patient with  immobilization at central hospital Sanglah Denpasar. Data was collecting by structural interview about their experience and expectation until hospitality. Sample was chose proportioned stratified random sampling. The analyzed by quadratic analysis where satisfaction rate measured by comparing evaluations based on experience and expectation. Correlation of self care service with patient satisfaction analyzed by One Way Anova and Regression Linier.Result: The study was found patient dissatisfy with quality of nursing service in aspect reliability, responsiveness, assurance, emphaty, and tangibles. Level of patient satisfaction was averrage 85,89%. There was significant relationship between degree of personal hygiene services with satisfaction (p<0,05). The regression linier found pattern: patient satisfaction= (79,307 + 11,672) X  clothed servicesConclusion: Nurse should be increasing nursing service concerned for hygiene patent to clothed.Keywords: personal hygiene services, patient satisfaction